Wiley Encyclopedia of Electrical and Electronics Engineering 2019
DOI: 10.1002/047134608x.w8392
|View full text |Cite
|
Sign up to set email alerts
|

Toward Ultradense Small Cell Networks: A Brief History on the Theoretical Analysis of Dense Wireless Networks

Abstract: This article provides dives into the fundamentals of dense and ultra-dense small cell wireless networks, discussing the reasons why dense and ultra-dense small cell networks are fundamentally different from sparse ones, and why the wellknown linear scaling law of capacity with the base station (BS) density in the latter does not apply to the former. In more detail, we review the impact of the following factors on ultradense networks (UDNs), (i) closed-access operations and line-ofsight conditions, (ii) the nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In UDNs, the BSs are positioned below the cluttered manmade structures, thus the radio signals in the line of sight (LoS) may encounter fewer absorption and diffraction losses than those in the non-line-of-sight (NLoS), leading to dissimilar path loss exponents. Hence, a widely used single-slope path loss model becomes inexact [37], [47]. The path loss model with multiple slopes where different distance ranges are susceptible to different path loss exponents eventually is desirable in modeling UDNs scenarios [40].…”
Section: B Channel Propagation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In UDNs, the BSs are positioned below the cluttered manmade structures, thus the radio signals in the line of sight (LoS) may encounter fewer absorption and diffraction losses than those in the non-line-of-sight (NLoS), leading to dissimilar path loss exponents. Hence, a widely used single-slope path loss model becomes inexact [37], [47]. The path loss model with multiple slopes where different distance ranges are susceptible to different path loss exponents eventually is desirable in modeling UDNs scenarios [40].…”
Section: B Channel Propagation Modelmentioning
confidence: 99%
“…For this reason, the cluster network topology varies from each UE due to different distances between cooperating BSs and the UE, which leads to dissimilar statistics of handovers. 2) Furthermore, the approaches in [32]- [34] have considered a standard path loss model in analyzing the impact of mobility on cooperative-based wireless networks, which is not realistic in dense wireless networks deployment [3], [37]. Besides, circumventing frequent reformation of cooperating BSs regarding high dense BS deployment and/or fast-moving UEs remains an open problem in the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting question is to ask about the asymptotic case, and the limits of network densification. In [73], it was observed that network densification is limited by the channel characteristics, and antenna heights. However, this result applies to networks operating over large areas and network settings that correspond to outdoor deployments, e.g., variable deployment heights of tens of meters above ground level.…”
Section: A Take Away Lessonsmentioning
confidence: 99%
“…Small cell deployment using lamp post in cities is a good example where users at outdoor street canyons maintain a LOS with the TX. Different coverage and capacity issues of small cells are studied in various studies [8], [9], however, no concrete strategy or limitation for ultra-dense deployment of small cells is provided. Especially impact of LOS connections on neighbor cell interference, and on the size of the area with bad signal to interference plus noise ratio (SINR) is not highlighted enough.…”
Section: Introductionmentioning
confidence: 99%